Efficiency Improvement of GaN-Based LEDs With a SiO(2) Nanorod Array and a Patterned Sapphire Substrate - Huang, H. W.; Huang, J. K.; Lin, C. H.; Lee, K. Y.; Hsu, H. W.; Yu, C. C.; Kuo, H. C. (My University, 2010)
The enhancement of light extraction from GaN-based light-emitting diodes (LEDs) with a patterned sapphire substrate (PSS) and a SiO(2) 12-fold photonic quasi-crystal (PQC) structure using nanoimprint lithography is presented. At a driving current of 20 mA on transistor-outline-can package, the light output powers of LED with a PSS and LED with a PSS and a SiO(2) PQC structure are enhanced by 35% and 48%, compared with the conventional LED. In addition, the higher output power of the LED with a PSS and a SiO(2) PQC structure is due to better reflectance on PSS and higher epitaxial quality on an n-GaN using a SiO(2) 12-fold PQC structure pattern. These results provide promising potential to increase output powers of commercial light-emitting devices.